FOXO1 promotes tumor progression by increased M2 macrophage infiltration in esophageal squamous cell carcinoma - Wang, Ying (Theranostics, 2020)
Objective: The transcription factor forkhead box protein O1 (FOXO1) is critical for regulating cytokine and chemokine secretion. However, its function in the tumor microenvironment (TME) remains largely unexplored. In this study, we characterized the prognostic value of FOXO1 and the interaction between tumor-derived FOXO1 and M2 macrophages in esophageal squamous cell carcinoma (ESCC). Methods: FOXO1 expression and macrophage infiltration in clinical samples and mouse models were quantified using quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry staining. Western blotting, qRT-PCR, and enzyme-linked immunosorbent assay were used to evaluate chemokine ligand 20 (CCL20) and colony stimulating factor 1 (CSF-1) expression in FOXO1(+) and FOXO1(-) tumor cells. Macrophage phenotypes were determined using qRT-PCR, flow cytometry, and RNA sequencing. Transcriptional activity was measured using chromatin immunoprecipitation (ChIP)-qPCR. Tumor viability was investigated using XTT proliferation and foci formation assays. Results: FOXO1 upregulation in tumor tissues was found to drive the polarization of M0 macrophages and infiltration of M2 macrophages into the TME, resulting in worse prognosis in ESCC patients. CSF-1, a vital factor inducing M0-to-M2 polarization, was upregulated via a FOXO1-mediated mechanism. RNA sequencing results corroborated that the FOXO1-induced macrophages exhibited similar molecular signatures to the IL4-stimulated M2 macrophages. The transwell assays showed that FOXO1 promoted the migration of M2 macrophages via CCL20 secretion, which could be inhibited using an anti-CCL20 antibody. FOXO1(+) tumor-induced M2 macrophages promoted tumor proliferation via the FAK-PI3K-AKT pathway and the PI3K inhibitor could effectively impede the oncogenical process. Conclusions: FOXO1 facilitated M0-to-M2 polarization and the recruitment of M2 macrophages in the TME via the transcriptional modulation of CCL20 and CSF-1. Our data deciphered the FOXO1-dependent mechanism in M2 macrophage infiltration in the TME of ESCC, which has implications for the development of novel prognostic and therapeutic targets to optimize the current treatment against ESCC.